2015
DOI: 10.1182/blood.v126.23.340.340
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Etoposide to CHOP Is Associated with Improved Outcome in Adult Anaplastic Large Cell Lymphoma Patients: A Nordic Lymphoma Group Study

Abstract: INTRODUCTION Anaplastic Large Cell Lymphomas (ALCL) are rare T-cell neoplasms grouped according to whether they express the fusion protein anaplastic lymphoma kinase (ALK+) or not (ALK-). ALK+ ALCL has consistently been found to have a favorable outcome compared to ALK- ALCL, but ALK+ ALCL is also associated with young age and other low risk features and not all studies have found ALK-expression to be an independent prognostic factor. In this population-based study, we aimed at analyzing the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…46 The Nordic Lymphoma Group also reported similar findings among 122 patients with ALCL, ALK-positive treated with the CHOEP regimen (5-year OS and PFS rates were 78% and 64%, respectively). 47 CHOEP regimen was associated with an improved OS in patients aged 41 to 65 years, even after adjusting for risk factors (P5.05). Bone marrow involvement was independently associated with poorer PFS in a multivariate analysis.…”
Section: Tcel-6mentioning
confidence: 97%
See 1 more Smart Citation
“…46 The Nordic Lymphoma Group also reported similar findings among 122 patients with ALCL, ALK-positive treated with the CHOEP regimen (5-year OS and PFS rates were 78% and 64%, respectively). 47 CHOEP regimen was associated with an improved OS in patients aged 41 to 65 years, even after adjusting for risk factors (P5.05). Bone marrow involvement was independently associated with poorer PFS in a multivariate analysis.…”
Section: Tcel-6mentioning
confidence: 97%
“…44 However, with the exception of ALCL, ALKpositive, outcomes are not optimal in other subtypes. 5,[45][46][47][48][49] In a retrospective analysis of 289 patients with PTCL treated within the DSHNHL trials, CHOEP was associated with an EFS benefit in ALCL, ALK-positive in patients younger than 60 to 65 years and also in patients with The NCCN Guidelines ® and this illustration may not be reproduced in any form without the express written permission of NCCN.…”
Section: First-line Therapymentioning
confidence: 99%
“…There are no published randomized trials comparing CHOP with other chemotherapy approaches for newly diagnosed sALCL. Retrospective studies support CHOEP in this context, the Nordic Lymphoma Group study reported improved survival outcomes (HR 0.48, 95% CI 0.32–0.74) when compared to CHOP in sALCL [ 9 , 17 ]. The T cell lymphoma project also reported a trend towards improved outcomes with etoposide regimens with superior 5-year OS (56% vs 69% for etoposide-containing regimens, p = 0.05) and a trend towards improved 5-year PFS (39% vs 50% for etoposide-containing regimens, p = 0.18) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies suggest that outcomes may be better than historical data with CHOP. [3][4][5] In a prospective trial, the Nordic group evaluated the role of autologous stem cell transplantation after patients achieved a CR/partial response with CHOEP. 6 At a median follow-up of 5 years, the 5-year progressionfree survival (PFS) and overall survival (OS) rates for AITL were 49% and 52%, respectively, and 38% and 47% for PTCL-NOS, respectively.…”
Section: Patient Case Study 1: Peripheral T-cell Lymphomamentioning
confidence: 99%